Pengembangan Daya Saing Usaha Kecil Unggulan Kota Bandung - Tresnawati, Yanti Susila; Iskandar, Trias Pyrenia; Abdurohim, Dindin; Ramadhan, Toto (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Binong Jati Knitting Industry Center, which is now better known as Kampoeng Radjoet, is one of Bandung's flagship products. This is shown: 1) Research results of Ina Primiana et al, Bandung Mayor Decree and Certificate of Local Lurah. Kampoeng Rajoet area has: 293 craftsmen, investment value 31,366 billion, production capacity per year 984,426 Lusin and provides employment for 2,143 laborers, regional and national target markets, several small businesses have entered the international market. One of them is Small Business Rajut owned by Eka Rahmat Jaya which is a PPPUD Partner located in the Binong Jati region, District, Batununggal, Bandung City which has the potential to be developed, but is still faced with the main problem, which is not yet having Business Competitiveness. Community service activities began to be carried out in March - September 2019. Priority problems faced by Partners to find a solution: 1) Problems do not have a Computerized Knitting Machine, limited raw materials ... 2) Marketing problems, 3) Management & HR Problems. 4) Problems with limited completeness of business and limited promotional media, 5) Limitations in participating in exhibitions and their completeness. This condition causes the target business partners do not have competitiveness. The approach method used, namely; Training, Technical Guidance (Bimtek), Assistance, Business facilitation. Outcomes of activities: Partners have capacity for Cixing machines and Raw material capacity, Increased Marketing Capacity / Market / consumer potential information: Segments, Targets and Positioning (STP), Business Management Capacity Building: Business Vision, Mission and Objectives and HR / Workforce increased motivation and creativity, Increased Capacity Completeness of business and Media Promotion: Product Branding, Internet Access, Neon Boxes, and can take part in Exhibitions (Expo) and have completeness (Paperbag Packaging / Bags, Banners, name cards, Brochures, Catalogs, Invoices, Mannequins and clothes hangers / hanger). The main thing of this program is that in accordance with its objectives, the Partners already have the ability to compete in running their businesses